Prevalence of Trypanosoma Evansi in Horses in Peninsular Malaysia. - Kumar, Amit (2009)
The main objective of this cross sectional study was to determine the prevalence of Equine Trypanosomes in Peninsula Malaysia involving Selangor, Kuala Lumpur, Johor, Negeri Sembilan, Pahang, Kelantan, Kedah, Melaka and to relate the prevalence and seroprevalence of Trypanosoma evansi in different breeds and sex. A total of 432 animals from different farms were involved in this study. A questionnaire was used to collect data on horse health and management practices. Four hundred thirty two blood samples in heparin from horses were tested for Trypanosoma sp using Haematocrit centrifugation technique, Staines thin film where three samples were found Positive. The plasma from all samples were tested for antibodies fo Trypanosoma using Card agglutination test for Trypanosomes (CATT). The prevalence of Trypanosomes using the parasitological techniques (HCT/BF) was 0.7% (3/432). The seroprevalence of Trypanosomes was 14.81% (64/432). Female horses showed zero prevalence of Trypanosoma evansi using parasitological method with all 224 blood samples negative while male horses showed 1.4% prevalence. Local thoroughbred horses showed highest seroprevalence (35.9%) while local cross breed showed lowest seroprevalence (3.5%). The state of Kedah showed the highest seroprevalence of equine trypanosomiasis (35.70%), while lowest seroprevalence was observed in Pahang (9.00%). This study showed that there is no high evidence of parasitemia in the sample. The seroprevalence however showed that 64 of horses had previously been infected or had previous exposure.